Innowacyjne biura zarządzania projektami - Wąsowicz, Marek (Innovation Offices of Project Management, 2006)
In this article innovation in Project Management Office (PMO) were described. First of all they are novelty in service of PMO, which rising the effectiveness of the project management. The main advantages and risk result from introduction Project Management Office in the company were also mentioned.The authors described also some result of poll concern application PMO in Polish company.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 189-195